Analisis Pengaruh Dukungan Keluarga Terhadap Edukasi Kesehatan Di Posyandu Lansia Wilayah Kerja UPTD Puskesmas Nambo Kabupaten Banggai Sulawesi Tengah - Dj Sanudin, Rindy Antika; Rahayu, Mesra; Herman, Sriyana; Yulis, Dian Meiliani; Rusli, Rusli (NHM PRESS, 2024)
Integrated Health Service for Elderly (called Elderly Posyandu) is a form of activity to handle the health of the elderly population. Elderly Posyandu offers activities in the form of health education to the elderly. The active role of the elderly's family is a supporting factor to make the elderly interested in participating in health education activities at the Posyandu. This study aims to analyze the influence of family support factors on the activeness of the elderly in participating in health education at the Elderly Posyandu in the working area of UPTD Puskesmas Nambo, Banggai Regency, Central Sulawesi. The type of research used is observational analytic with a cross-sectional research design. Data collection using a questionnaire. The sample in this study was 95 elderly people in the Working Area of UPTD Puskesmas Nambo, Banggai Regency, Central Sulawesi. Data analysis using the chi-square test. The results of this study indicate that there is an influence of emotional support (p = 0.000), appreciation support (p = 0.000), informational support (p = 0.000) and instrumental support (p = 0.000) on the activeness of the elderly in participating in health education at the UPTD Nambo Health Center, Banggai Regency, Central Sulawesi. Most respondents have high family support and are active in participating in health education at the Elderly Posyandu. The results of this study are expected to be a reference for health workers and families to provide support to the elderly, especially to participate in health education at the Posyandu.